Do Manuscrito ao Livro Impresso II (Coimbra University Press, 2025)
This book continues the project of publishing the contributions arising from the Lecture Series "From manuscript to printed book", now bringing together, in a second volume, the studies of the third and fourth editions (2017/18 and 2018/19), which took place at the Department of Languages and Cultures of the University of Aveiro, within the scope of the Degree in Languages and Editorial Studies and the Master in Editorial Studies. The purpose of this initiative is to foster and deepen the articulation between research and teaching, providing students with a privileged contact with the multiple aspects of the History of Books and Publishing. The close collaboration between the Department of Languages and Cultures and the Coimbra University Press has made it possible to extend the scope of this formative and investigative action to professional practice, since the MA students who complete their curricular internship in the publishing house are involved in the editing of the works. The studies in the present volume, subjected to a rigorous refereeing process, deal with various topics in the History of Books and Publishing and are one of the most visible results of a project that is being renewed and which aims to contribute to the dissemination of the Arts of the Book.